Pengaruh Terapi Reminiscence terhadap Harga Diri Lansia dengan Penyakit Kronik di Kelurahan Bubulak Tahun 2012 - Utami, Tantri Widyarti; Ariani, Ni Putu (Jurnal Keperawatan Jiwa, 2014)
Old age is the final stage of the human life cycle. At this stage, individuals experience a setback various functions and capabilities, resulting in older adults experiencing chronic disease that affects the elderly dignity. The purpose of this research is to gain influence reminiscence therapy for the dignity of elderly with chronic diseases in Bubulak Village Bogor in 2012. The benefit of this research is as a guide for the nurses in conducting reminiscence therapy in the elderly with chronic diseases and as an evidence based. The hypothesis of this study is that “reminiscence therapy can increase self-esteem of elderly with chronic diseases”. The design used was